O Programa Nacional de Bioinsumos no âmbito da Política Nacional de Agroecologia e Produç\~ao Orgânica: Origem, contribuiç\~oes e potencialidades - Mariana Aquilante Policarpo; Regina Helena Rosa Sambuichi; Fabio Alves; Carla Gualdani; Daniela Aparecida Pacífico (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The National Policy on Agroecology and Organic Production (PNAPO) was established in 2012 with the primary aim of integrating, articulating, and adapting governmental actions aimed at promoting agroecology and organic production in Brazil. The National Bioinputs Program (PNB) was instituted in 2020 with the goal of expanding and strengthening the use of bioinputs in the country. The need for the creation of the PNB was raised during the discussions promoted throughout the implementation of the PNAPO, and the creation of this program was included among the actions planned for this policy. This work retrieves the context of the emergence of the PNB within the strategies of the PNAPO and the main results of its first years of implementation to understand to what extent the directions taken by the program, after its institution, are contributing or not to the objectives of this policy. Additionally, the study proposes to identify opportunities for the PNB to effectively contribute to the PNAPO, maximizing its benefits for the development and strengthening of Brazil's organic and agroecological agriculture. The methodology used was based on a literature review, document analysis, and collection of primary and secondary data. As a result, it was observed that the weakening of the PNAPO and the disarray of its execution mechanisms, mainly from the extinction of its management bodies in 2019, resulted in changes in the design and focus of the PNB in relation to what had been thought in its original conception. Thus, the scope of the program expanded to also include conventional agriculture, especially crops oriented towards agribusiness. This led to a deviation from the central objective of the program, which was initially to broaden access to bioinputs to strengthen organic and agroecological production. The program, therefore, did not prioritize investment in actions aimed at this end, which limited its potential contribution to this policy. Therefore, for the PNB to achieve the main objective for which it was originally conceived, and considering that bioinputs are important tools to enable these production systems, it is essential to restore instances of dialogue between government bodies and civil society to ensure social control and participation in the plans and actions of the PNB, as well as the appropriate allocation of budgetary resources. In addition, it is fundamental to promote greater coordination between the management bodies of the PNAPO and the PNB, aligning public policies with the demands of the sector, so that the implementation of the program is aligned with the objectives of the PNAPO.
Keywords: Q18; 330; National Agroecology and Organic Farming Policy; National Program for Bioinputs; organic farming and agroecology; bioinputs; government-civil society dialogue